Comparative analysis of transport media for isolating Shigella - Lesmana, Murad; Salim, Oktavianus Ch.; Herwana, Elly; Bukitwetan, Paul; Surjawidjaja, Julius E (Universa Medicina, 2008)
Transport media for Shigella include buffered glycerol saline (BGS), and Cary-Blair (CB). However being a liquid medium BGS may leak or spill during transport and thus may cause contamination. The other concern is the 30% concentration of glycerol in the BGS which may be inhibitory to some susceptible Shigella species. This study was conducted to determine the best and safe transport media for Shigella. Rectal swab samples were obtained from 289 dysenteric patients and transported to the laboratory in Cary-Blair (CB) transport medium, standard buffered glycerol saline (BGS), BGS with the addition of 0.5% agar (BGS-A), and BGS with the addition of 0.5% agar and reduced glycerol to 15% (BGS-M). Recovery rates between CB, BGS, BGS-A and BGS-M and their combinations were compared. The overall prevalence of Shigella recovered from any of the four tubes was 24.9% (72/289). CB and BGS-M recovered Shigella in 54 out of 289 patients (18.7%), CB and BGS-A in 50 (17.3%), and CB and BGS in 49 (17.0%), while CB, BGS, BGS-A, and BGS-M alone gave positive Shigella in 30 (10,4%), 29 (10.0%), 34 (11.8%) and 46 (15.9%), respectively. This study suggests that a minor modification to the BGS raised the recovery rate of Shigella.